SCAFFOLDING IN SECOND LANGUAGE TEACHING: EFFECTIVENESS, STRATEGIES, AND PRACTICAL APPLICATIONS - Natia Katamadze; Lali Tavadze; Ivdit Diasamidze (International Journal of Innovative Technologies in Social Science, 2025)
In this article, a mixed-methods approach was employed to assess the effectiveness of scaffolding as a technique in second language teaching. The study involved both qualitative and quantitative data collection methods. A thorough review of existing literature on scaffolding in second language education was conducted. The review focused on understanding the theoretical foundations, key strategies, and challenges associated with scaffolding. Classroom observations were conducted in language learning environments where scaffolding techniques were implemented. Observations focused on teacher-student interactions, the use of scaffolding methods, and the overall classroom atmosphere. Semi-structured interviews were conducted with language teachers who implemented scaffolding techniques in their lessons. The interviews aimed to gather insights into teachers’ experiences, the challenges they faced, and their perceptions of scaffolding’s effectiveness. Surveys were distributed to students who participated in scaffolding-based lessons. The surveys assessed their perceptions of the learning process, including engagement, comprehension, and language skill improvement. Student surveys indicated a high level of engagement and motivation in classrooms where scaffolding was used. Students reported that the interactive nature of scaffolding made the learning process more enjoyable and effective. Classroom observations revealed that scaffolding techniques facilitated more frequent and meaningful teacher-student interactions. Teachers were able to provide targeted support based on individual students’ needs, which contributed to a more personalized learning experience. While scaffolding proved effective, some challenges were noted. Teachers reported difficulties in maintaining the appropriate level of support for each student without overwhelming them. Additionally, limited class time and large class sizes made it challenging to provide individualized scaffolding to all students. The research highlighted that scaffolding allows for differentiated learning, where instruction can be tailored to meet the varying needs of students. This was especially beneficial in mixed-ability classrooms, where students could progress at their own pace. The findings confirm that scaffolding is an effective technique for enhancing second language learning. It promotes active engagement, improves comprehension, and helps students achieve greater language proficiency. The research demonstrates that scaffolding can be successfully implemented in a variety of classroom settings. Teachers can use different scaffolding strategies, such as providing prompts, using visuals, and offering feedback, to support students at different stages of their learning. Future studies could explore the long-term effects of scaffolding on second language acquisition, especially in different cultural or educational contexts. Additionally, examining the impact of digital tools and technology on scaffolding in language learning could provide valuable insights. Based on the findings, it is recommended that language teachers incorporate scaffolding techniques into their lessons to foster a more interactive and supportive learning environment. Teachers should also be mindful of the challenges involved and seek ways to balance the level of support provided to each student.